Analisis Sistem Antrian Loker Pada Salah Satu Perpustakaan di Jakarta - Supani, Rina; Fitriani, Risma (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
The library is an important information resource center for the surrounding community. This analysis aims to improve efficiency and service quality, as well as increase visitor satisfaction. The results of the analysis show the average rate of arrival and service of visitors, waiting time in the queue, and the number of visitors in the system. The average visitor arrival rate is 6.34 and 6.44 arrivals per minute, while the average visitor service rate is 19.63 and 19.65 service minutes per person. In one hour, the average number of visitors waiting in the queue is about 6.6696 and 7.234 (7) visitors, with an average waiting time of about 1.05 and 1.12 minutes. This data forms the basis for designing recommendations for improvements to improve the efficiency of the locker queuing system and the visitor experience in the library